‘I’ve heard wonderful things about you’: how patients compliment surgeons - Hudak, Pamela L. (2010)
This investigation was motivated by physician reports that patient compliments often raise ‘red flags’ for them, raising questions about whether compliments are being used in the service of achieving some kind of advantage. Our goal was to understand physician discomfort with patient compliments through analyses of audiotaped surgeon-patient encounters. Using conversation analysis, we demonstrate that both the placement and design of compliments are consequential for how surgeons hear and respond to them. The compliments offered after treatment recommendations are neither designed nor positioned to pursue institutional agendas and are responded to in ways that are largely consistent with compliment responses in everyday interaction, but include modifications that preserve surgeons’ expertise. In contrast, some compliments offered before treatment recommendations pursue specific treatments and engender surgeons’ resistance. Other compliments offered before treatment recommendations do not overtly pursue institutionally-relevant agendas—for example, compliments offered in the opening phase of the visit. We show how these compliments may but need not foreshadow a patient’s upcoming agenda. This work extends our understanding of the interactional functions of compliments, and of the resources patients use to pursue desired outcomes in encounters with healthcare professionals.